Adherence in paediatric renal failure and dialysis: an ethical analysis of nurses' attitudes and reported practice. Issue 2 (10th January 2014) - Mellor, Joe Scott; Hulton, Sally-Anne; Draper, Heather
Abstract : Minors have difficulty adhering to the strict management regimen required whilst on renal dialysis for chronic renal failure. This leads to ethical tensions as healthcare professionals (HCPs) and parents try, in the minor's best interests, to ensure s/he adheres. All 11 dialysis nurses working in a large, regional paediatric dialysis unit were interviewed about their perceptions and management of non-adherence and the ethical issues this raised for them. Participants reported negative attitudes to non-adherence alongside sympathy and feelings of frustration. They discussed the competing responsibilities between nurses, parents and minors, and how responsibility ought to be transferred to the minor as s/he matures; the need for minors to take responsibility ahead of transferring to adult services; and, the process of transferring this responsibility. Our discussion concentrates on the ethical issues raised by the participants' reports of how they respond to non-adherence using persuasion and coercion. We consider how understandings of capacity, traditional individual autonomy, and willpower can be used to comprehend the issue of non-adherence. We consider the relational context in which the minor receives, and participates in, healthcare. This exposes the interdependent triad of relationships between HCP, parent and minor and aids understanding of how to provide care in an ethical way. Relational ethics is a useful alternative understanding for professionals reflecting upon how they define their obligations in this context.